2015
DOI: 10.1002/cam4.601
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidoreductase in cancer: more than a differentiation marker

Abstract: Human xanthine oxidoreductase (XOR) catalyzes the last two steps of purine catabolism and is present in two interconvertible forms, which may utilize O2 or NAD + as electron acceptors. In addition to uric acid, XOR products may comprise reactive oxygen and nitrogen species that have many biologic effects, including inflammation, endothelial dysfunction, and cytotoxicity, as well as mutagenesis and induction of proliferation. XOR is strictly modulated at the transcriptional and post‐translational levels, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
100
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 70 publications
7
100
0
1
Order By: Relevance
“…XOR, a housekeeping enzyme, is known as the rate‐limiting enzyme in purine catabolism, and is predominantly expressed in the liver . Multiple lines of evidence have determined that XOR functions as a multifunctional enzyme and is involved in various physiological and pathological responses, including cancer . Fiorenzo et al first reported that the expression of XOR was significantly elevated in livers with virus‐related cirrhosis and that low XOR activity was detected in HCC tissue compared with the adjacent peritumor .…”
Section: Discussionmentioning
confidence: 99%
“…XOR, a housekeeping enzyme, is known as the rate‐limiting enzyme in purine catabolism, and is predominantly expressed in the liver . Multiple lines of evidence have determined that XOR functions as a multifunctional enzyme and is involved in various physiological and pathological responses, including cancer . Fiorenzo et al first reported that the expression of XOR was significantly elevated in livers with virus‐related cirrhosis and that low XOR activity was detected in HCC tissue compared with the adjacent peritumor .…”
Section: Discussionmentioning
confidence: 99%
“…An annual decrease or increase in serum urate was associated with a 2.3-and 1.6-fold increased risk of cancer mortality, respectively. Prior studies on serum urate with cancer mortality have yielded conflicting results [14,29,44,[50][51][52][53][54], with some reporting lower risk [51,52]and some reporting increased risk [14,29,44,53,54] of cancer mortality. Potential explanations for these inconsistent findings include not being able to examine both low and high serum urate levels, incomplete covariate adjustment, and inability to examine changes in serum urate with cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation and upregulation of XOR activity have been related to different types of solid tumors [47], suggesting the importance of XOR produced ROS in tumorigenesis [48]. Besides, a higher XOR activity has been related with relapsed acute myeloid leukemia [49].…”
Section: Discussionmentioning
confidence: 99%